Retrospective evaluation of 28 cases of inflammatory linear verrucous epidermal nevus - Buğra Burç Dağtaş; Vildan Manav; Cem Leblebici; Ayse Esra Koku Aksu (Turkderm Turkish Archives of Dermatology and Venereology, 2025)
Background and Design: Inflammatory linear verrucous epidermal nevus (ILVEN) is a rare, chronic dermatosis characterized by linear erythematous scaly plaques following Blaschko's lines. This study aims to comprehensively evaluate ILVEN cases, focusing on demographic, clinical, and histopathological features to improve understanding of its presentation and management. Materials and Methods: This retrospective cross-sectional study included 28 patients diagnosed at our center with clinically and histopathologically confirmed ILVEN between 2011 and 2022. Data on patient demographics, age at lesion onset, duration before diagnosis, lesion location, histopathological findings, and treatment approaches were collected from hospital records and supplemented by patient interviews. Results: Our study had a male predominance (63.4%), with a median age of lesion onset at 7.5 years and a median age of 14 years, indicating a prolonged delay in diagnosis. The mean duration from lesion onset to diagnosis was 9.86 years. Lesions were most frequently located on the lower extremities, following a Blaschkoid distribution, with 73.3% of patients reporting pruritus. Key histopathological findings included orthokeratosis with hypergranulosis (60.7%), parakeratosis overlying hypogranulosis (46.4%), and psoriasiform epidermal hyperplasia (46.4%). Topical corticosteroids were the primary treatment modality, while spontaneous regression was observed in 14.3% of untreated cases. Conclusion: This study highlights the clinical and histopathological features of ILVEN, emphasizing the importance of early recognition in reducing diagnostic delays. Further research is warranted to enhance understanding of ILVEN's clinical course and to optimize diagnostic and therapeutic strategies.